Splicing defective mutants of the COXI gene of yeast mitochondrial DNA: initial definition of the maturase domain of the group II intron aI2. - Moran, J V (1994)
Six mutations blocking the function of a seven intron form of the mitochondrial gene encoding subunit I of cytochrome c oxidase (COXI) and mapping upstream of exon 3 were isolated and characterized. A cis-dominant mutant of the group IIA intron 1 defines a helical portion of the C1 substructure of domain 1 as essential for splicing. A trans-recessive mutant confirms that the intron 1 reading frame encodes a maturase function. A cis-dominant mutant in exon 2 was found to have no effect on the splicing of intron 1 or 2. A trans-recessive mutant, located in the group IIA intron 2, demonstrates for the first time that intron 2 encodes a maturase. A genetic dissection of the five missense mutations present in the intron 2 reading frame of that strain demonstrates that the maturase defect results from one or both of the missense mutations in a newly-recognized conserved sequence called domain X.